2019
DOI: 10.1292/jvms.19-0280
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study on intercurrent pancreatitis with <i>Babesia gibsoni</i> infection in dogs

Abstract: Babesia rossi infection has been reported to be associated with the high prevalence of pancreatitis in dogs. In this study, we retrospectively investigated whether pancreatitis occurs in B. gibsoni-infected dogs. The clinical manifestations, and hematological and serum biochemical examination results, including canine pancreatic-specific lipase (cPL), in 20 B. gibsoni-infected dogs were analyzed. The cPL concentration exceeded 400 µg/l in only 2 dogs, and they were suspected of having pancreatitis. Although th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…An additional study documented that 28% of dogs with a B. rossi infection had an increased serum cPLI concentration 36 . Other babesia species (eg, B. gibsoni ) have been implicated in the development of AP, albeit at a lower prevalence 35 . Potential mechanisms include hypotension, secondary immune‐mediated hemolytic anemia, hemoconcentration, and alterations in lipid metabolism 34 .…”
Section: Etiology and Potential Risk Factors For Pancreatitismentioning
confidence: 99%
See 1 more Smart Citation
“…An additional study documented that 28% of dogs with a B. rossi infection had an increased serum cPLI concentration 36 . Other babesia species (eg, B. gibsoni ) have been implicated in the development of AP, albeit at a lower prevalence 35 . Potential mechanisms include hypotension, secondary immune‐mediated hemolytic anemia, hemoconcentration, and alterations in lipid metabolism 34 .…”
Section: Etiology and Potential Risk Factors For Pancreatitismentioning
confidence: 99%
“…Diabetes mellitus, 12,24,25ac Hereditary/breed predispositions SPINK 1 mutation, 26,27b Acute: Terrier breeds, miniature poodles, dachshunds, cocker spaniel, Alaskan malamute, laika, miniature schnauzer 12,[28][29][30][31] Chronic: Cavalier King Charles spaniel, collies, boxers 32 Lipid disorders Hypertriglyceridemia 28,29,33 Miscellaneous Babesiosis [34][35][36] Canine monocytic ehrlichiosis 37 Schistosomiasis (Heterobilharzia americana) [38][39][40] Honeybee envenomation 41 Organic acidemias 42 Immunoglobulin G4-related disease 43,44 Increasing age 12 Obesity/overweight status 5,12 Neutered status 5,12 Previous surgery 5 Hepatitis/cholangitis 45 Note: Potential risk factors for AP in dogs. Many of these factors are implied by a temporal association alone and causation has not been established for many of these factors.…”
Section: Dietary Factorsmentioning
confidence: 99%
“…Pancreatic lipase concentrations are increased in several infectious diseases including parvovirus gastroenteritis, babesiosis, and monocytic ehrlichiosis 103‐106 . Pancreatic lipase concentrations also may be increased in dogs with intervertebral disc disease, foreign bodies and gastric‐dilatation and volvulus 49,107‐109 .…”
Section: Pancreatic Lipase Concentrations In Dogs With Primary Diseases Other Than Pancreatitismentioning
confidence: 99%
“…Pancreatic lipase concentrations are increased in several infectious diseases including parvovirus gastroenteritis, babesiosis, and monocytic ehrlichiosis. 103 , 104 , 105 , 106 Pancreatic lipase concentrations also may be increased in dogs with intervertebral disc disease, foreign bodies and gastric‐dilatation and volvulus. 49 , 107 , 108 , 109 These increases in pancreatic lipase concentration may be secondary effects on the exocrine pancreas associated with the primary disease condition.…”
Section: Pancreatic Lipase Concentrations In Dogs With Primary Diseases Other Than Pancreatitismentioning
confidence: 99%
“…Several studies have reported increased serum lipase concentrations or activities in primary extrapancreatic disorders such as renal, gastrointestinal, cardiac, or endocrine diseases; neoplasia; infections; intervertebral disc disease; and portal hypertension or even chronic use of corticosteroids. 2,26,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] Although the exact cause for elevated lipase concentrations or activities is unknown, it could be due to several reasons, such as the presence of concurrent subclinical or clinical pancreatitis in study cohorts, either as a comorbidity or sequalae of the primary disease of interest. An accurate determination of concurrent pancreatitis, especially in the face of similar clinical signs, is challenging due to the inherent nature of the traditional gold standard (ie, histopathology) for a diagnosis of pancreatitis.…”
Section: Effects Of Extrapancreatic Lipases On Analytical Specificity...mentioning
confidence: 99%